Pengaruh Modal Kerja, Skala Usaha dan Akses Pembiayaan Terhadap Profitabilitas UMKM di BUMDesa Pesona Klumprit, Mojolaban Sukoharjo - Ummu Kaltsum; Setyaningsih SU (Teewan Journal Solutions, 2026)
This study aims to analyze the effect of working capital, business scale, and access to financing on the profitability of MSMEs in BUMDesa Pesona Klumprit, Mojolaban, Sukoharjo. Using a quantitative approach, this study took a sample from the entire population, namely 34 MSME actors, through a census or saturated sampling technique. Data were collected using questionnaires and analyzed using descriptive analysis, multiple linear regression, t-test, F-test, and coefficient of determination (R2). The results show that access to financing has a positive and significant effect on MSME profitability. However, working capital and business scale were found to have a positive but insignificant effect. These findings indicate that simply having large capital and business size does not guarantee increased profitability without efficient management. Conversely, ease of access to financing sources proved to be a crucial factor that directly improved the financial performance of MSMEs. Thus, this study suggests that MSME empowerment programs should not only focus on capital distribution, but also on managerial assistance and expansion of targeted access to financing to ensure sustainable growth.